Bahasa & Perkembangan Literasi pada Anak Usia Dini: Sebuah Studi Literatur - Ulfa Masfufah (Alzam: Journal of Islamic Early Childhood Education, 2021)
Language is one of the domains of individual development. Language development is related to literacy skills, both from the beginning of life as well as in later times. Individual literacy abilities are related to academic achievement. Early childhood in the early stages of pre-school is the basis for the introduction and understanding of basic children's literacy. Therefore the concept of development and also efforts to maximize the potential for children's development is in accordance with their uniqueness. Because of its importance, this article will discuss developments related to language and literacy in children and the methods used in efforts to develop children's language skills and literacy.